Performance Comparison of Native and Hybrid Android Mobile Applications Based on Sensor Data-Driven Applications Based on Bluetooth Low Energy (BLE) and Wi-Fi Communication Architecture - Aleksander Kaczmarczyk; Piotr Zając; Wojciech Zabierowski (Energies, 2022)
In the age of smartphones and tablets, the popularity of mobile applications is rising extremely quickly. There are countless purposes for using them, such as communication, social media, news, sending emails, shopping, paying, watching videos and streams, and playing games. Google’s Android is currently the most frequently used mobile system in the world. The main aim of this article is to compare native and hybrid mobile applications created for this system, taking into account the needs and challenges of designing systems using BLE and Wi-Fi. The comparison was based on mobile applications implemented in the Java 8 language and the Ionic framework. The aim was to compare the efficiency of data processing in both technologies, in order to indicate dependencies that can help in the selection of technologies in the projects under development based on BLE, Wi-Fi and sensor networks.